Exploration of Course Ideological and Political Reform in Cultural and Art Courses Empowered by the Metaverse - Fu, Bing (Advances in Social Sciences Research Journal, 2024)
Course ideological and political education, as an important part of moral education and talent cultivation in higher education, reflects the fundamental purpose of higher education in teaching and educating people. The ideological and political education in cultural and artistic courses in universities should adapt to the development of digital technology and innovate teaching methods, and combine the development of the metaverse and service design thinking to carry out ideological and political education reform. The article combines the background of the metaverse era, from classroom teaching to online teaching to practical teaching, to explore how to better utilize the metaverse to reform ideological and political education in cultural and artistic courses. By combining the metaverse context to enhance the effectiveness of ideological and political education in cultural and artistic courses, and by expanding the functions of the metaverse platform and designing teaching methods to comprehensively enhance students' comprehensive literacy, it promotes the reform of ideological and political education in higher education courses and serves the high-quality development process of national economic, social, and cultural construction.